Exposure to “I’m from Bariga” YouTube Posting and Its Influence on Female Students in Chukwuemeka Odumegwu Ojukwu University Hostels - Nwabueze , Chinenye; Odishika , Emmanuel; Ejikeme , Abel (African Journal of Education,Science and Technology (AJEST), 2017)
Influence of “I’m from Bariga” YouTube posting on students in female hostels is an exploratory research into the disciplinary composure of female students living in Chukwuemeka Odumegwu Ojukwu University, hostels, in Igbariam Campus. This study sets out to ascertain whether the female students are exposed to the “I’m from Bariga” video, if the video influence their disciplinary composure in the hostels and to find out if their exposure makes them want to stop violent acts. The research adopted the Survey Method while Focus Group Discussion was employed as the tool in extracting information from the hostellers. The study was based on the Catharsis Theory and Selective Retention Theory. Findings show that female students in COOU hostels were positively influenced by the video and as such behaved in the best possible manner. The researcher therefore, recommended that universities set up unified basic internet access through which students access the social media with terms and conditions